Documentation of traditional housing in Mayangna communities. Bosawás Biosphere Reserve, Nicaragua - Cimadomo, Guido; González Meixuero, Nathalia; Jamauca, José Luis; Castaño Gil, Carlos; Martín Sánchez, Marta (My University, 2020)
The Mayangna ethnic community populate the UNESCO Bosawás Biosphere Reserve in the north of Nicaragua, in the North Caribbean Coast Autonomous Region. During the volunteer program developed by the School of Architecture at the University of Malaga, Spain. in the summer of 2019, the architecture of a traditional Mayangna house in Santa María (Bonanza municipal term) was documented. Documentation and digital reconstruction of this typology is still inadequate and this is considered a crucial task given that many of these traditional buildings are at risk of disappearing, as the comparison with more recent buildings in Sakalwas (Bonanza) shows. The paper describes, focusing on a typological and construction analysis, the original houses and the domestic culture of this community, characterized by the use of pressed bamboo for the external walls and Suita palm leaves for the roofs. Other characteristics are the lack of internal distribution and the use of piles to elevate the single roof from the ground. A slow process of transformation has been detected, leading to increased environmental costs and less effective solutions for combating tropical climatology and heavy raining periods. Finally, we discuss how the active protection of the Biosphere Reserve should be compatible with the preservation of traditional houses, for a more socially and environmentally sustainable future.
Keywords: Vivienda vernácula; Arquitectura vernácula- Congresos; Vernacular dwelling; Mayangna; Heritage Documentation; North Caribbean Coast Autonomous Region; Nicaragua